Surging money supply in China : a study on causes & the monetary policy undertaken. - Lim, Monica Kim Eng. (2008)
This paper examines the determinants behind the surge in money supply in China from the period 1999 to 2007. The monetary policy undertaken by the People's Bank of China on curbing the growth of broad money is also evaluated.